Presentation is loading. Please wait.

Presentation is loading. Please wait.

Rearranging algebraic Formulae

Similar presentations


Presentation on theme: "Rearranging algebraic Formulae"— Presentation transcript:

1 Rearranging algebraic Formulae
Use mouse click after each slide

2 Example1 H=8e + 2, Make e the subject of the formulae
Lets see how we got H. . . in H=8e + 2 Start with e Multiply all by 8 x8 Add 2 +2 We get H Do the exact opposite to get e . . We get e Divide all by 8 ÷8 Subtract 2 -2 Start with H So e=(H-2)÷8 or e= (H-2) 8 Your turn: Make a the subject of the formula F=6a +5

3 Example 2 V=7(c+9)+ 10, Make c the subject of the formulae
Lets see how we got V. . . In V=7(c+9)+10 Start with c Add 9 +9 Multiply all by 7 x7 We get V Add 10 +10 Do the exact opposite to get c . . We get c Minus 9 -9 Divide all by 7 ÷7 Start with V Minus 10 -10 So c=(V-10)÷7 -9 or c= (V-10) - 9 7 Your turn: Make z the subject of the formula F=6(z+9) + 8

4 Example 3 T=(s+4)2+ 3, Make s the subject of the formulae
Lets see how we got T In T=(s+4)2+3 Start with s Add 4 +4 Squared all ( )2 We get T Add 3 +3 Do the exact opposite to get s . . We get s Minus 4 -4 Square root all Start with T Minus 3 -3 So s=(T-3)√ -4 or s= √(T-3) - 4 Your turn: Make p the subject of the formula F=(p+9)2 + 8

5 Example 4 X =(Y+5) - 6, Make Y the subject of the formulae 7
Lets see how we got X. . . Start with Y Add 5 +5 Divide all by 7 ÷7 We get X minus 6 -6 Do the exact opposite to get Y . . We get Y Minus 5 -5 Multiply all by 7 x7 Start with X Add 6 +6 So Y=(X+6)x7 -5 or Y=7(X+6) - 5 Your turn: Make g the subject of the formula F= (g+9) - 7 5

6 Example 5 T=4(u2+7), Make w the subject of the formulae
Lets see how we got T In T=4(u2+7) Start with u Square it u2 Add 7 +7 We get T Multiply all by 4 x4 Do the exact opposite to get w . . We get u Minus 7 -7 Square root All √ Start with T Divide by 4 ÷ 4 So u=(T÷4 -7)√ or u= T – 7 4 Your turn: Make p the subject of the formula F=5(p2 + 8)

7 Answers 1. Make a the subject of the formula F=6a +5
Restart 1. Make a the subject of the formula F=6a +5 a=(F-5)÷6 or a= (F-5) 6 2. Make z the subject of the formula F=6(z+9) + 8 z=(F-8)÷6 -9 or z= (F-8) - 9 6 3. Make p the subject of the formula F=(p+9)2 + 8 So p=(F-8)√ or p= √(F-8) - 9 4. Make g the subject of the formula F= (g+9) - 7 5 g=(F+7)x5 -9 or g=5(F+7) - 9 5. Make p the subject of the formula F=5(p2 + 8) So p=(F÷5 -8)√ or p= F – 8 5


Download ppt "Rearranging algebraic Formulae"

Similar presentations


Ads by Google